2016
DOI: 10.1177/0004563216661737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the point of care Afinion AS100 analyser in a community setting

Abstract: Background A 'one stop shop' model for multifactorial risk factor management in a culturally sensitive environment may improve cardiovascular disease and diabetes prevention. A full biochemical profile for cardiovascular disease risk assessment includes a lipid profile, glucose, glycated haemoglobin and urine albumin creatinine ratio measurements. This may require the use of more than one point of care testing instrument. Methods Individuals who attended a community cardiovascular disease risk screening or an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
(18 reference statements)
3
21
2
Order By: Relevance
“…Our study is one of two suggesting that the Afinion is an acceptable POC tool for the measurement of lipids. Our findings support those of Jain et al, [5] who compared the Afinion with the Cholestech LDX for the measurement of TC, HDL-C and triglyceride levels. The Afinion was shown to meet the performance criteria recommended by the National Education Cholestrol Program in the UK for TC and HDL-C measurements.…”
Section: Researchsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study is one of two suggesting that the Afinion is an acceptable POC tool for the measurement of lipids. Our findings support those of Jain et al, [5] who compared the Afinion with the Cholestech LDX for the measurement of TC, HDL-C and triglyceride levels. The Afinion was shown to meet the performance criteria recommended by the National Education Cholestrol Program in the UK for TC and HDL-C measurements.…”
Section: Researchsupporting
confidence: 92%
“…In the present study, the researchers also found that the Afinion detected HbA1c levels that were above target levels. Similar findings were reported by Jain et al, [5] with the Afinion being shown to overestimate HbA1c levels for certain samples. However, similar to the present study, the overestimation did not affect the overall diagnostic performance of the instrument.…”
Section: Researchsupporting
confidence: 89%
See 3 more Smart Citations